Television in contemporary Asia - French, David (Ed.); Richards, Michard (Ed.) (New Delhi Sage, 2000)
Television in contemporary Asia presents origional discussions on the most recent developments in Asian television systems in the context of the continually changing global environment.this volumes also covers Hongkong,Indonessia,Japan,Korea,Malaysia,Paki
Keywords: Television broadcasting-Asia-Cross-Cultural studies; Television broadcasting-Asia-Influence; Globalization